The Effect of Constructive Patriotism on Constructive Thinking Ability in Historical Learning at Students of Senior High School Muhammadiyah Karanganyar Indonesia - Syuhada Ginting, Arief; Joebagio, Hermanu; Dyah S I, Cicilia (ASEAN Journal of Education, 2023)
This study analyzed the effect of constructive patriotism on constructive thinking ability in historical learning. The study used a quantitative research method with a descriptive correlational approach. To find out the effect of predictors on the dependent variable, the measurement was made by simple linear regression tests. The research sample consisted of 106 students at ages 16 to 18 years old which were taken by a purposive sampling technique in Senior High School Muhammadiyah 1 Karanganyar. The result show that there is a partial effect of constructive patriotism on constructive thinking ability with 18.88 percentage of correlation. It can be said that the constructive attitude of patriotism went hand in hand with the constructive thinking ability. The conclusion states that the attitude of constructive patriotism and constructive thinking ability are competencies that need to be taught to students by historical learning.